Weight-bearing CT Technology in Musculoskeletal Pathologies of the Lower Limbs: Techniques, Initial Applications, and Preliminary Combinations with Gait-Analysis Measurements at the Istituto Ortopedico Rizzoli - Leardini, Alberto; Durante, Stefano; Belvedere, Claudio; Caravaggi, Paolo; Carrara, Claudio; Berti, Lisa; Lullini, Giada; Giacomozzi, Claudia; Durastanti, Gilda; Ortolani, Maurizio; Guglielmi, Giuseppe; Bazzocchi, Alberto (Seminars in Musculoskeletal Radiology, 2019)
Musculoskeletal radiology has been mostly limited by the option between imaging under load but in two dimensions (i.e., radiographs) and three-dimensional (3D) scans but in unloaded conditions (i.e., computed tomography [CT] and magnetic resonance imaging in a supine position). Cone-beam technology is now also a way to image the extremities with 3D and weight-bearing CT. This article discusses the initial experience over a few studies in progress at an orthopaedic center. The custom design of total ankle replacements, the patellofemoral alignment after medial ligament reconstruction, the overall architecture of the foot bones in the diabetic foot, and the radiographic assessment of the rearfoot after subtalar fusion for correction of severe flat foot have all taken advantage of the 3D and weight-bearing feature of relevant CT scans. To further support these novel assessments, techniques have been developed to obtain 3D models of the bones from the scans and to merge these with state-of-the-art gait analyses.
Keywords: cone-beam CT; weight-bearing; three-dimensional bone models; gait analysis; plantar pressure